Problem‐solving therapy reduces subjective burden levels in caregivers of family members with mild cognitive impairment or early‐stage dementia: Secondary analysis of a randomized clinical trial. (17th April 2019) - Garand, Linda; Morse, Jennifer Q.; ChiaRebecca, Lichun; Barnes, Jennifer; Dadebo, Victoria; Lopez, Oscar L.; Dew, Mary Amanda
Abstract : Objectives: Interventions addressing burden have limited impact among long‐term family caregivers. We examined whether problem‐solving therapy (PST) would reduce burden levels of caregivers of individuals diagnosed with mild cognitive impairment (MCI) or early‐stage dementia (AD). Methods: Caregivers (N = 73) randomly received PST or nutritional training (NT). Burden measures were assessed over 1‐year post‐intervention. Results: Relative to NT, caregivers receiving PST endorsed improved perceived burden levels over time, regardless of the type of caregiver. Distress over the care recipient's dementia‐related behaviors remained low over time among MCI caregivers receiving PST, while these burden levels among MCI caregivers receiving NT rose over time. AD caregivers receiving PST endorsed reductions in these burden levels over time, while AD caregivers in the NT group endorsed higher burden levels over time. Conclusion: PST, taught early in the caregiving trajectory, improves subjective burden levels among caregivers of family members with relatively mild cognitive deficits.